Sejarah Tradisi Pantauan Mangkal Luagh di Kedurang dan Relevansinya dengan Pembelajaran Sejarah di SMA - Fenny D Widyastuti; Een Syaputra; Gaya Mentari (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to reconstruct the history of the pantauan tradition of mangkal laugh in the Kedurang Village, South Bengkulu and analyze its relevance to learning history in high school. The research was conducted using historical methods consisting of four main stages: heuristics, source criticism, interpretation and historiography. The results of the study show that: 1) the pantauan tradition of mangkal laugh is a tradition rooted in the pantauan tradition in the Besemah area, Pagar Alam. The tradition of monitoring mangkal luagh has existed in Kedurang for a long time. At least since before Indonesia's independence; 2) since it was first carried out until now, the pantauan tradition of mangkal luagh has undergone three changes in form. These changes occurred mainly in terms of the number of executors and the form of implementation of Mangkal Luagh; 3) in relation to learning history in high school, for the Indonesian History subject there is no material that directly intersects with the Pantauan Mangkal Luagh tradition. This is because the mangkal luagh tradition does not have links with prehistoric, Hindu-Buddhist, Islamic or Western-influenced traditions. However, the mangkal luagh tradition can be integrated into learning history of interest, especially on the theme of historical thinking, historical source and historical research methods (for grade X) and the theme of the development of Indonesian culture in new order and reformation era (for grade XII).